Warfare and shamanism in Amazonia - Fausto, Carlos (Cambridge Latin American studies, 2012)
Warfare and Shamanism in Amazonia is an ethnographic study of the Parakanã, a little-known indigenous people of Amazonia, who inhabit the interfluvial region in the state of Pará, Brazil. This book analyzes the relationship between warfare and shamanism in Parakanã society from the late nineteenth century until the end of the twentieth century. Based on the author's extensive fieldwork, the book presents first-hand ethnographic data collected among a generation still deeply involved in conflicts. The result is an innovative work with a broad thematic and comparative scope.